Evaluasi Kesehatan Ibu pada Kehamilan Risiko Tinggi di Desa Buntalan, Klaten - Hartati, Lilik; Wahyuningsih, Endang; Wahyuningsih, Astri; Ambarsari, Lusiana (Universitas Muhammadiyah Klaten, 2025)
High-risk pregnancies, which pose significant threats to maternal and fetal health. The maternal mortality rate in Indonesia remains high, caused by both direct and indirect factors occurring during pregnancy and childbirth, particularly the history of previous pregnancies and childbirths. The aim of this study is to evaluate the maternal health of high-risk pregnant women by focusing on their pregnancy and childbirth history in Buntalan Village. This study is a quantitative research with a descriptive research type. The sample for this study consisted of 14 high-risk pregnant women, using a total sampling technique. The research instrument used in this study is a questionnaire. Data analysis was performed to obtain an overview of the frequency distribution and percentage of previous pregnancy and childbirth history. Most mothers (64.0%) consulted healthcare providers for their pregnancies, with the majority (57.1%) having their first check-up in the first trimester, which is essential for early detection and management of conditions. Although many mothers attended at least two antenatal visits and took iron supplements to prevent anemia. The majority of previous deliveries were assisted by obstetricians (64.3%), with most mothers experiencing spontaneous delivery (50%) and a smaller proportion undergoing Caesarean sections (14.2%). While only 7.1% of mothers faced complications during delivery, a significant number of babies (64.3%) had low birth weights and experienced complications at birth. The need for greater attention to maternal nutrition during pregnancy and improvements in the quality of prenatal and intranatal care. Education on monitoring newborn health is also crucial.